Cross-reactivity of SARS-CoV structural protein antibodies against SARS-CoV-2 - Bates, Timothy A. (Cell Rep, 2021)
In the ongoing coronavirus disease 2019 (COVID-19) pandemic, there remain unanswered questions regarding the nature and significance of the humoral immune response toward other coronavirus infections. Here, we investigate the cross-reactivity of antibodies raised against the first severe acute respiratory syndrome coronavirus (SARS-CoV) for their reactivity toward SARS-CoV-2. We extensively characterize a selection of 10 antibodies covering all of the SARS-CoV structural proteins: spike, membrane, nucleocapsid, and envelope. Although nearly all of the examined SARS-CoV antibodies display some level of reactivity to SARS-CoV-2, we find only partial cross-neutralization for the spike antibodies. The implications of our work are two-fold. First, we establish a set of antibodies with known reactivity to both SARS-CoV and SARS-CoV-2, which will allow further study of both viruses. Second, we provide empirical evidence of the high propensity for antibody cross-reactivity between distinct strains of human coronaviruses, which is critical information for designing diagnostic and vaccine strategies for COVID-19.